2015
DOI: 10.1017/ice.2015.187
|View full text |Cite|
|
Sign up to set email alerts
|

In the Endemic Setting, Clostridium difficile Ribotype 027 Is Virulent But Not Hypervirulent

Abstract: BACKGROUND Conflicting reports have been published on the association between Clostridium difficile ribotypes and severe disease outcomes in patients with C. difficile infection (CDI); several so-called hypervirulent ribotypes have been described. We performed a multicenter study to assess severe disease presentation and severe outcomes among CDI patients infected with different ribotypes. METHODS Stool samples that tested positive for C. difficile toxin were collected and cultured from patients who presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[32] Our cohort study indicated disease severity and outcomes similar to those seen with ribotype 014-020, but was limited by sample size. Additionally, ribotype 255 was correlated with much lower odds of severe CDI compared to ribotype 027 [22]. Patients infected with ribotype 027 were older and with more comorbidities compared to those infected with ribotype 255, potentially indicating a bias in who is infected with each ribotype.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[32] Our cohort study indicated disease severity and outcomes similar to those seen with ribotype 014-020, but was limited by sample size. Additionally, ribotype 255 was correlated with much lower odds of severe CDI compared to ribotype 027 [22]. Patients infected with ribotype 027 were older and with more comorbidities compared to those infected with ribotype 255, potentially indicating a bias in who is infected with each ribotype.…”
Section: Discussionmentioning
confidence: 95%
“…Samples were plated onto selective cefoxitin-cycloserine-fructose agar (CCFA) plates (Anaerobe Systems, Morgan Hill, CA) and anaerobically incubated for 48-72 h for culture. Characteristic C. difficile colonies were tested using latex agglutination reagent (Oxoid, Hampshire, England) and presence of triose phosphate isomerase and toxin genes was determined using multiplex PCR [22]. Fluorescent PCR ribotyping was performed as previously described [23].…”
Section: Collection Culture and Typingmentioning
confidence: 99%
“…However, some “hypervirulent” attributes of ribotype 027 vary across strains (e.g., degree of toxin production and sporulation (22)) or are found in ribotypes not typically associated with increased disease severity (e.g., fluoroquinolone resistance (23)), making it difficult to pinpoint specific mechanisms responsible for increased incidence and/or severity of infection with ribotype 027 strains. Correspondingly, some clinical studies (24-26) failed to reproduce statistically significant increases in severe CDI in patients infected with ribotype 027 observed in other studies (13, 27, 28). Finally, even as the frequency of ribotype 027-associated CDI has stabilized or decreased in some regions (29, 30), the overall frequency of CDI has remained high, with other C. difficile ribotypes increasing in prevalence (29- 32).…”
Section: History Of C Difficile Infectionmentioning
confidence: 87%
“…In a similar study of 715 CDI patients in 7 hospitals in Houston, TX, ribotype 027 strain CDI (23.8% of total cases) was an independent predictor of both severe CDI and severe outcome CDI (adjusted odds ratios of 2.24 and 1.71, respectively) when considering a comparison to all other CDI case ribotypes in aggregate (10). No logistic regression model was able to establish any single ribotype as a significant predictor for severe CDI or outcome; in fact, 3 other non-027 ribotypes had point estimates of severe CDI outcome as high as or higher than ribotype 027 in this study (10). A European study noted that ribotype 078 CDI had higher observed mortality than other lineages, including ribotype 027 (11).…”
mentioning
confidence: 92%
“…In a single-center cross-sectional study of 743 CDI patients in Michigan, ribotype 027 was associated with severe CDI in an unadjusted analysis, but this ribotype was not associated with severe CDI when considering 11 other covariates; only leukocytosis and serum albumin level were associated with severe CDI in an adjusted logistic regression model (9). In a similar study of 715 CDI patients in 7 hospitals in Houston, TX, ribotype 027 strain CDI (23.8% of total cases) was an independent predictor of both severe CDI and severe outcome CDI (adjusted odds ratios of 2.24 and 1.71, respectively) when considering a comparison to all other CDI case ribotypes in aggregate (10). No logistic regression model was able to establish any single ribotype as a significant predictor for severe CDI or outcome; in fact, 3 other non-027 ribotypes had point estimates of severe CDI outcome as high as or higher than ribotype 027 in this study (10).…”
mentioning
confidence: 96%